ACTIVATED CARBON UTILIZATION FROM CORN COB (Zea mays) AS A HEAVY METAL ADSORBENT IN INDUSTRIAL WASTE - Christica, IS; Julia, R (Asian Journal of Pharmaceutical Research and Development, 2018)
Corn is a diet staple for many people in the world. It’s found as a side dish, in soup, in casseroles, and more. The use of corn as a food ingredient also increase corn production which is also leaves cobs waste that has not been optimally utilized. Therefore to increase the economic value and utilization of this plant, the corn cobs can be utilized as a bio absorbent through activation process. The purpose of this study was to reduce the concentration of heavy metal using activated carbon from corn cobs and also to determine the effect of the addition of activated carbon in various concentrations to heavy metal content. Determination of heavy metal absorption of Ferrous, Copper and Lead in industrial waste was using Inductively Coupled Plasma (ICP). Result showed that addition of 1 gram corn cob activated carbon decreased level of ferrous, copper and lead as much as 60.20%; 59.24% and 59.67% respectively. The addition of 1.5 gram corn cob activated carbon decreased level of ferrous, copper and lead as much as 80.01%, 79.5% and 79.89 % respectively It could be conculded that activated carbon form corn cobs decreased heavy metal content in industrial waste.